2015
DOI: 10.1111/jce.12771
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Lead Placement Targeted at the Latest Activated Site Guided by Electrophysiological Mapping in Coronary Sinus Branches Improves Response to Cardiac Resynchronization Therapy

Abstract: LV lead placed at the latest activated site guided by EPM resulted in a significantly greater CRT response, and a shorter QRS duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…A suboptimal LV pacing site is one of the reasons for nonresponse to CRT . Several studies have suggested that pacing the LV in a site with late activation (either mechanical or electrical) may improve the hemodynamic response, reverse remodeling and clinical outcome of CRT recipients . Zanon et al .…”
Section: Discussionmentioning
confidence: 99%
“…A suboptimal LV pacing site is one of the reasons for nonresponse to CRT . Several studies have suggested that pacing the LV in a site with late activation (either mechanical or electrical) may improve the hemodynamic response, reverse remodeling and clinical outcome of CRT recipients . Zanon et al .…”
Section: Discussionmentioning
confidence: 99%
“…Different pacing algorithms to reduce intraventricular, interventricular, and atrioventricular dyssynchrony is a continuous field of research in postimplantation period. Regarding implantation factors, position of CS lead and its proximity to the latest activated LV area was found to be a very important factor for CRT response (Liang et al., ; Rad et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have prospectively measured QLV have thus far used 3D mapping systems or have moved the permanent LV pacing lead from site to site. [5][6][7][8]12 The present study describes a simplified method to measure QLV intervals using a unipolar guidewire during CRT implantation that does not require pairing with a 3D mapping system or repeated maneuvering of an LV pacing lead. The QLV measured with the guidewire corresponds closely with the value measured following placement of the lead.…”
Section: Discussionmentioning
confidence: 99%
“…This study was not designed or powered to follow patients for clinical response, since the relationship between QLV and CRT response rate is well established. 3,8 The present study did not seek to identify the site of the longest QLV in each patient, but sites with a QLV > 95 ms were identified in 19 out of 20 patients. This study nonetheless demonstrates the feasibility of making QLV measurements without an electroanatomic mapping system and prior to the selection of the final LV pacing lead.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation